2022
DOI: 10.3389/fmicb.2022.865141
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Protein Homeostasis Network in Bacillus subtilis

Abstract: Protein homeostasis is fundamental to cell function and survival. It relies on an interconnected network of processes involving protein synthesis, folding, post-translational modification and degradation as well as regulators of these processes. Here we provide an update on the roles, regulation and subcellular localization of the protein homeostasis machinery in the Gram-positive model organism Bacillus subtilis. We discuss emerging ideas and current research gaps in the field that, if tackled, increase our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 161 publications
0
5
0
Order By: Relevance
“…The system allows for the inducible production of synthetic fluorescently trackable PAs (GFP(Sp)-cI78 EP8 ), and provides suitable control strains that produce soluble variants (GFP(Sp)-cI78 WT and GFP(Sp)). Previous attempts at making fluorescent PA reporters in B. subtilis have mainly involved fluorescently tagging components of the proteostatic network that are thought to colocalize to PAs (e.g., the protease ClpP and its unfoldases ClpC, ClpX and ClpE) [ 28 , 29 , 30 , 31 ]. However, in the light of later research that showed that many fluorescent fusion proteins commonly used to study cellular localization have an innate tendency to trivially assemble in foci [ 32 ], it remains unclear whether these fluorescent PA reporters represent the native behavior of the proteostatic components and/or PAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system allows for the inducible production of synthetic fluorescently trackable PAs (GFP(Sp)-cI78 EP8 ), and provides suitable control strains that produce soluble variants (GFP(Sp)-cI78 WT and GFP(Sp)). Previous attempts at making fluorescent PA reporters in B. subtilis have mainly involved fluorescently tagging components of the proteostatic network that are thought to colocalize to PAs (e.g., the protease ClpP and its unfoldases ClpC, ClpX and ClpE) [ 28 , 29 , 30 , 31 ]. However, in the light of later research that showed that many fluorescent fusion proteins commonly used to study cellular localization have an innate tendency to trivially assemble in foci [ 32 ], it remains unclear whether these fluorescent PA reporters represent the native behavior of the proteostatic components and/or PAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the light of later research that showed that many fluorescent fusion proteins commonly used to study cellular localization have an innate tendency to trivially assemble in foci [ 32 ], it remains unclear whether these fluorescent PA reporters represent the native behavior of the proteostatic components and/or PAs. Additionally, these proteostasis components have known roles in important cellular functions such as sporulation [ 28 , 31 , 33 , 34 , 35 , 36 , 37 , 38 ] and competence [ 39 ], which could be perturbed when these proteins are fluorescently tagged without adequate validation. Fluorescently labeled malate dehydrogenase (Mdh) has also been utilized to visualize subcellular PAs because Mdh is known to unfold and co-aggregate with PAs upon heat stress [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, individual cells in a bacterial populations age due to damage to vital cell components such as DNA and proteins. DNA damage can often be repaired using precise or error‐prone DNA repair mechanisms; however, protein damage is more complex and the proteostasis network (Figure 3 ) constantly monitors the proteome to help maintain protein homeostasis (Balchin et al, 2016 ; Matavacas & von Wachenfeldt, 2022 ). In addition to damage, many proteins have a functional ‘shelf life’, and specific degradation signals are incorporated into proteins whose activities are required to fulfil a specific function during a prescribed period of time (e.g.…”
Section: The Proteostasis Networkmentioning
confidence: 99%
“…This response varies between the model organisms for Gram-negative and Gram-positive bacteria, Escherichia coli , and Bacillus subtilis . In E. coli , the expression of cytosolic chaperones and proteases is transcriptionally activated by the heat shock sigma factors H. In contrast, the expression of chaperones and proteases in B. subtilis is regulated by the transcriptional repressors CtsR and HrcA, the transcriptional regulator Spx and the general stress sigma factor B (SigB), which are discussed later in this review (Hecker et al 1996 , Lim and Gross 2010 , Elsholz et al 2017 , Schramm et al 2020 , Matavacas and von Wachenfeldt 2022 ).…”
Section: Introductionmentioning
confidence: 99%